Jealous females? Female competition and reproductive suppression in a wild promiscuous primate. Issue 1886 (5th September 2018) - Baniel, Alice; Cowlishaw, Guy; Huchard, Elise
Abstract : Female–female competition over paternal care has rarely been investigated in promiscuous mammals, where discreet forms of male care have recently been reported despite low paternity certainty. We investigated female competition over paternal care in a wild promiscuous primate, the chacma baboon ( Papio ursinus ), where pregnant and lactating females establish strong social bonds (friendships) with males that provide care to their offspring. We tested whether pregnant and lactating females interfere with the sexual activity of their male friend to prevent new conceptions that might lead to the subsequent dilution of his paternal care. We found that pregnant and lactating females were more aggressive towards oestrous females when they had recently conceived themselves, and when the oestrous female was mate-guarded by, and showed greater sexual activity with, their male friend. This aggression also reduced the likelihood of conception of the targeted female. These findings indicate that females can aggressively prevent further conceptions with their offspring's carer through reproductive suppression. Competition over access to paternal care may play an important and underestimated role in shaping female social relationships and reproductive strategies in promiscuous mammalian societies.